Building Renovation, but Makes Sense. Critical Review of Economic and Environmental Aspects. (31st May 2016) - Sobolewski, Mario
Abstract: In this paper, the contradictions between the theoretical savings potential, the requirements of the legislator, the pollutants in and around the existing building and the real waste of resources represented. Here Furthermore, the health risks and the corresponding risks explains what approvingly, whether knowingly or unknowingly, every builder takes into account, as these are standard in almost all buildings available or installed. It has become difficult to environmentally friendly to build or rehabilitate.